Female condom use in the rural sex industry in China: analysis of users and non-users at post-intervention surveys. - Liao, Susu; Weeks, Margaret R; Wang, Yanhong; Li, Fei; Jiang, Jingmei; Li, Jianghong; Zeng, Xiaomei; He, Bin; Dunn, Jennifer (AIDS care, 2011)
Changes in sexual attitudes and behaviors and resurgence of the sex industry in China have increased concerns about HIV/AIDS and sexually transmitted infections (STI) epidemics. Little attention has been paid to the significant and growing sex industry in rural China. Promotion of barrier protection in this context is most effective to prevent STIs and pregnancy. The female condom (FC) is a barrier method that gives women more autonomy in its application, and has other advantages, but has been little promoted and tested in high risk contexts in China. The China/US Women's Health Project was designed to promote FC use in addition to male condoms (MC) through outreach intervention conducted in sex work establishments in rural and small urban towns in southern China, using the original prototype FC1. The study used quantitative and qualitative methods to document the pre-intervention context, intervention delivery process, and post-intervention outcomes of FC use. In this paper we compare post-intervention FC users and non-users in the first study sites, two rural towns in a single county in Hainan Province. Examination of cross-sectional six-month and 12-month surveys indicated that, despite relatively high MC use, about one-third of the women in sex work establishments in these rural towns had adopted FC at each post-intervention survey. Compared with non-users, FC users were more likely to be freelance women in boarding houses, more sexually experienced, married with children, more sexually active in the prior month, and more exposed to the intervention. The rural context hampered intervention implementation, particularly the significant limits in health and human resources available to manage prevention of HIV/STIs among women in the sex industry. These challenges highlight the need to better understand the context of the rural sex industry and capacity of local resources for better prevention efforts and the benefits that new prevention technologies like FC can offer.
Keywords: Adolescent; Adult; China; Condoms, Female; Female; Health Knowledge, Attitudes, Practice; HIV Infections; Humans; Middle Aged; Prostitution; Risk Factors; Rural Health; Safe Sex; Sexually Transmitted Diseases; Young Adult